Magnetic particles for sugar separation from sulphuric acid solution generated during nano‐crystalline cellulose production. (7th December 2017) - Sarma, Saurabh J.; Ayadi, Mariem; Maiti, Sampa; Brar, Satinder K.; Berry, Richard
Abstract: Nano‐crystalline cellulose (NCC) is a renewable material having different applications ranging from drug delivery to a reinforcing filling agent in polymer synthesis. Concentrated sulphuric acid is used to hydrolyze cellulosic biomass to obtain NCC. Manufacturers are keen to reuse the diluted acid solution left after the process. However, the presence of mono and oligosaccharides makes it unsuitable for repeated use. About 99 % of these compounds have been successfully separated from the acid solution by employing NaOH‐treated magnetic particles developed during this investigation. It has been observed that by NaOH treatment, zeta potential of the magnetic particles could be increased from +11 mV to +37.5 mV; correspondingly, sugar removal efficiency was increased from 23.04 % to more than 99 %. Thus a direct correlation between the change in zeta potential of the particles and sugar separation efficiency has been observed.